Homofermentative Lactobacilli isolated from organic sources exhibit potential ability of lactic acid production - Stephen, Jain Maria; Saleh, Arabi Mohammed (Frontiers in Microbiology, 2023)
There has been an increasing interest in recent years in lactic acid bacteria that are derived from organic sources for lactic acid production. This research article presents the isolation and identification of homofermentative lactic acid bacteria from various organic sources, followed by qualitative and quantitative analysis of lactic acid produced. A total of 32 isolates were identified initially from various sources, such as Curd (C1, C2), Probiotics (P1, P2, and P3), Silage (Si1 and Si2), Soil samples (S1, S2, and S3) Vermicompost (V1 and V2) and Farmyard manure. Biochemical tests such as Gram’s staining, Catalase test and Oxidase test were conducted for preliminary identification of lactic acid bacteria using De Man, Rogosa and Sharpe agar (MRS) media. Through selection and identification, based on colony morphology and biochemical characteristics, 18 isolates were identified as lactic acid bacteria. The subsequent analysis included a Tube test, screening for organic acid production and Homofermentative screening using Homofermentative-Heterofermentative Differential (HHD) medium for Qualitative analysis of Lactic acid. The results revealed that 9 out of 18 selected strains were homofermentative and had promising potential for the production of lactic acid. Furthermore, six isolates (P1-1, S1-3, C2-1, V2-3, P2-1,C1-1) from all of the 9 positive strains were subjected to pH testing (0, 24, 48, 72 h) and Titrimetric assay for estimation of % crude Lactic acid present. The presence of Lactic acid was confirmed using Thin Layer Chromatography (TLC) L (+)-Lactic acid was quantified using K-LATE enzymatic assay kit, for best 3 isolates (P1-1, S1-3, C2-1). Finally, the strains were subjected to 16SrRNA sequencing and were identified as Lactobacilli. Based on the findings of the study, it could be concluded that homofermentative lactic acid bacteria with significant LA-producing ability can be obtained from different organic sources and may prove to be useful in the successful production of lactic acid for biotechnological applications.